2007
DOI: 10.1002/pd.1762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2407 fetuses in a Turkish population

Abstract: Postmortem evaluation is useful to detect findings necessary for genetic counseling. Our protocol is effective especially in fetuses with congenital anomalies but it can detect only some of the fetal reasons in IUFD cases. A more detailed protocol is needed to investigate IUFD cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
2
15
0
2
Order By: Relevance
“…Pathologic evaluation of D&E specimens for midtrimester IUFD has not been studied in the literature to our knowledge. However, there are several recent studies [58][59][60][61][62][63] that have examined the value of pathologic examination of the fetus and placenta for intact fetuses in setting of IUFD, and the American College of Obstetricians and Gynecologists 64 recommends autopsy and placental evaluation be offered for all stillbirths. A study of the Stillbirth Collaborative Research Network 58 involving 663 stillbirths in both the second and third trimesters, and including postmortem examinations in more than 500 patients, showed that 66% of stillbirths have at least 1 positive result among the 3 major components of the evaluation: perinatal autopsy, placental examination, or karyotype.…”
Section: 54mentioning
confidence: 99%
“…Pathologic evaluation of D&E specimens for midtrimester IUFD has not been studied in the literature to our knowledge. However, there are several recent studies [58][59][60][61][62][63] that have examined the value of pathologic examination of the fetus and placenta for intact fetuses in setting of IUFD, and the American College of Obstetricians and Gynecologists 64 recommends autopsy and placental evaluation be offered for all stillbirths. A study of the Stillbirth Collaborative Research Network 58 involving 663 stillbirths in both the second and third trimesters, and including postmortem examinations in more than 500 patients, showed that 66% of stillbirths have at least 1 positive result among the 3 major components of the evaluation: perinatal autopsy, placental examination, or karyotype.…”
Section: 54mentioning
confidence: 99%
“…Two studies demonstrate the utility of pathologic examination of an intact IUFD specimen after a labor induction. A Turkish study 5 of 2407 intact pregnancy terminations included 759 IUFD specimens between 10-and 24-weeks' gestation. Pathologists documented abnormal findings in 14.3% of specimens (n ¼ 112 of 759) and findings other than congenital anomalies in 9.6% of specimens (n ¼ 73 of 759), although the number identified through autopsy versus surgical examination was not included.…”
Section: Resultsmentioning
confidence: 99%
“…5 Since modern ultrasound technology identifies many morphologic abnormalities, researchers have questioned the added value of a pathologic examination. 6,7 However, most second-trimester patients have not yet undergone a full anatomic ultrasound evaluation at the time of fetal demise.…”
mentioning
confidence: 99%
“…it has been shown through some studies that these can be reduced substantially by means of improved prenatal, obstetric and postnatal care (1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, clinicians, geneticists, pediatric surgeons, radiologists and pathologists are required to be consulted for certain diagnosis of anomalies as well as the application of right methods so as to overcome such cases (1). a further issue to be dealt with thoroughly is the implications of anomalies in fetuses for future pregnancies.…”
Section: Introductionmentioning
confidence: 99%